Altitude patterns of seed C, N, and P concentrations and their stoichiometry in an alpine meadow on the eastern Tibetan Plateau - Jia, Nan; Niklas, Karl J.; Yao, Buqing; Wang, Zhiqiang (Frontiers in Ecology and Evolution, 2022)
Understanding the altitudinal patterns of plant stoichiometry in seeds is critical for characterizing important germination and dormancy strategies, soil seed bank composition, seed predation probability, efficiency of seed dispersal and seedling performance, and to predict how biodiversity might be influenced by climate change. However, our understanding of the altitudinal patterns of seed stoichiometry is extremely limited. This study aims to explore the altitudinal patterns of seed C:N:P stoichiometry. We measured the concentrations of C, N and P in the seeds of 253 herbaceous species along an altitudinal transect (2000-4200 m) on the eastern Tibetan Plateau, China, to quantify C:N:P stoichiometry. The geometric means of C, N, and P concentrations were 569.75 mg/g, 34.76 mg/g, and 5.03 mg/g, respectively. The C:N, C:P, and N:P ratios were 16.39, 113.31, and 6.91, respectively. The seed C, N, and P concentrations and C:N:P ratios varied widely among major plant groups and showed significant altitudinal trends. In general, C, N, and P concentrations increased, whereas seed C:N:P ratios decreased with elevation. These results inform our understanding of the altitudinal patterns of seed stoichiometry and how to model ecosystem nutrient cycling.